2022
DOI: 10.3847/psj/ac42c9
|View full text |Cite
|
Sign up to set email alerts
|

Col-OSSOS: Probing Ice Line/Color Transitions within the Kuiper Belt’s Progenitor Populations

Abstract: Dynamically excited objects within the Kuiper Belt show a bimodal distribution in their surface colors, and these differing surface colors may be a tracer of where these objects formed. In this work, we explore radial color distributions in the primordial planetesimal disk and implications for the positions of ice line/color transitions within the Kuiper Belt’s progenitor populations. We combine a full dynamical model of the Kuiper Belt’s evolution due to Neptune’s migration with precise surface colors measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…First, it has been shown that the so-called blue binaries, a population of optically blue contaminants found in the orbital region of the otherwise optically red cold classicals, could only have moved a few au during the phase of Neptune's migration in order to preserve their 100% binary fraction (Fraser et al 2017(Fraser et al , 2021Nesvorný et al 2022). In our proposed scenario, where the color versus inclination correlation stems from a composition gradient in the protoplanetary disk, this may pose a contradiction for the blue binaries that possess small values of PC 1 (and small s/s nir ), which would suggest a formation of these binaries at the inner edge of the protoplanetary disk, i.e., several au away from the transition line between the BrightIR and FaintIR populations (Nesvorný et al 2020;Ali-Dib et al 2021;Buchanan et al 2022). Reconciling the presence of blue binaries among cold classical objects with our proposed idea of a composition gradient in the BrightIR formation region would require a precise measurement of the location of the transition line between the formation regions of BrightIR and FaintIR TNOs, and dynamical simulations of Neptune's migration able to displace the blue binaries across the full BrightIR formation region while preserving their binarity, low inclinations, and low eccentricities.…”
Section: Origins Of the Color-dynamical Structurementioning
confidence: 87%
“…First, it has been shown that the so-called blue binaries, a population of optically blue contaminants found in the orbital region of the otherwise optically red cold classicals, could only have moved a few au during the phase of Neptune's migration in order to preserve their 100% binary fraction (Fraser et al 2017(Fraser et al , 2021Nesvorný et al 2022). In our proposed scenario, where the color versus inclination correlation stems from a composition gradient in the protoplanetary disk, this may pose a contradiction for the blue binaries that possess small values of PC 1 (and small s/s nir ), which would suggest a formation of these binaries at the inner edge of the protoplanetary disk, i.e., several au away from the transition line between the BrightIR and FaintIR populations (Nesvorný et al 2020;Ali-Dib et al 2021;Buchanan et al 2022). Reconciling the presence of blue binaries among cold classical objects with our proposed idea of a composition gradient in the BrightIR formation region would require a precise measurement of the location of the transition line between the formation regions of BrightIR and FaintIR TNOs, and dynamical simulations of Neptune's migration able to displace the blue binaries across the full BrightIR formation region while preserving their binarity, low inclinations, and low eccentricities.…”
Section: Origins Of the Color-dynamical Structurementioning
confidence: 87%
“…To date the most comprehensive analyses of KBO formation locations are Nesvorný et al (2020) and Buchanan et al (2022). They consider only two classes of object, the LR and VR objects, with CCKBOs being considered members of the latter.…”
Section: The Orbital Distributions and Origins Of Faintir And Brighti...mentioning
confidence: 99%
“…Nesvorný et al (2020) compared the red and very red population distributions from these simulations to the thenavailable observational constraints, and they determined that the observed distribution was consistent with a transition in the initial planetesimal disk from an inner red population to an outer very red population occurring between 30 and 40 au. Buchanan et al (2022) tested initial particle distributions of red and very red TNOs distributed within 30 au, and found both combinations (red or very red as the inner type, and the other as the outer type) to provide an acceptable match to the observed current color distribution, with inner/outer color transitions at 27-28 au. These analyses all utilized optical colors to differentiate between red and very red surfaces instead of a combination of optical and NIR slopes; however, a significant fraction of the objects can be properly classified with only the optical slope.…”
Section: Introductionmentioning
confidence: 99%